The "STICKINESS" of stigma: guilt by association after a friend's arrest - Tinney, Erin (Criminology, 2023)
Prior research has examined the consequences of one's police contact, but the consequences of vicarious police contact are not as well known. This study expands on labeling theory and the concept of "stickiness" by assessing whether a friend's arrest increases the likelihood of one's police contact. Using a sample of rural youth (N = 13,170), I find that a friend's arrest is associated with an increase in the likelihood of one's first arrest the next year after accounting for other predictors of police contact. Based on my theoretical framework, I interpret this finding as "guilt by association." In addition, ending relationships with friends who have been arrested does not significantly impact this relationship. This study concludes that police contact may be harmful for a youth's social network and builds on the concept of stickiness by suggesting that stigma not only sticks from one individual to another but may also stay despite efforts to end one's association with the arrested individual. The study expands on preexisting research on the consequences of adolescent police contact by introducing a friend's police contact as a way in which an individual may be more likely to become involved in the justice system.